THE USE OF INTERACTIVE TEACHING METHODS IN TEACHING ENGLISH TO SENIOR SECONDARY SCHOOL STUDENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
English has become one of the most important international languages, playing a significant role in education, business, science, and communication. Consequently, English language teaching has shifted from traditional teacher-centered instruction to more student-centered and interactive approaches. Interactive teaching methods encourage learners to actively participate in classroom activities, improve communication skills, and develop higher-order thinking abilities. This paper explores the importance
Keywords: Interactive teaching methods, English language teaching (ELT), senior secondary school students, communicative language teaching (CLT), learner-centered approach, classroom interaction, pair work, group work, role-play, classroom discussion, debate, brainstorming, project-based learning (PBL), task-based learning (TBL), collaborative learning, active learning, language acquisition, speaking skills, listening skills, reading comprehension, writing skills, communicative competence, critical thinking, creativity, motivation, educational technology, digital learning, student engagement, language proficiency, foreign language education.